2022
DOI: 10.1155/2022/6498794
|View full text |Cite
|
Sign up to set email alerts
|

Micronutrient Level Is Negatively Correlated with the Neutrophil-Lymphocyte Ratio in Patients with Severe COVID-19

Abstract: Aim. To explore the potential relationship between NLR and micronutrient deficiency in patients with severe COVID-19 infection. Methods. Sixteen patients were categorized into the mild group (mild COVID-19) and severe group (severe COVID-19) based on the guideline of the management of COVID-19. The lactate dehydrogenase (LDH); superoxide dismutase (SOD), the inflammatory markers (neutrophil lymphocyte ratio (NLR)), erythrocyte sedimentation rate (ESR), c-reactive protein (CRP), selenium (Se), iron (Fe), zinc (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The earliest clinical observational study correlating selenium levels with COVID-19 severity was performed at the Qilu Hospital of Shandong University (China) between 27 January and 18 May 2020 [ 53 ]. The authors concluded that “micronutrients should be considered in the treatment of COVID-19, especially in critically ill patients”.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The earliest clinical observational study correlating selenium levels with COVID-19 severity was performed at the Qilu Hospital of Shandong University (China) between 27 January and 18 May 2020 [ 53 ]. The authors concluded that “micronutrients should be considered in the treatment of COVID-19, especially in critically ill patients”.…”
Section: Resultsmentioning
confidence: 99%
“…The authors concluded that “micronutrients should be considered in the treatment of COVID-19, especially in critically ill patients”. However, the study lacked controls and involved only 16 patients (8 mild and 8 severe) with different ages and BMIs (statistically different between the two COVID-19 severity groups) [ 53 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since the COVID-19 pandemic spread around the world, some studies have been published trying to link Se-deficiency with the disease severity ( Table 3 ). The general interest in Se and COVID-19 has been attributed to its protective role against some viruses and as a modulator of the immune system and inflammatory responses [18] , [19] , [34] , [40] , [196] , [199] , [231] , [232] , [233] , [234] , [235] , [236] , [237] , [238] , [239] , [240] . To date, few clinical studies have indicated a possible causal relation between Se-deficiency and SARS-CoV-2 infection [241] .…”
Section: Se Viral Infection and Viral Replicationmentioning
confidence: 99%
“…Selenium studies on the neutrophil-to-lymphocyte ratio (NLR), an index of systemic inflammation [ 61 , 62 , 63 , 64 ], have also indicated interrelationships with Se homeostasis. Selenium and other micronutrients have been negatively correlated with NRL levels in patients with COVID-19 [ 65 ], indicating the protective role of selenium supplementation in severe inflammatory conditions.…”
Section: Introductionmentioning
confidence: 99%